2007
DOI: 10.1002/masy.200750444
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Performances of Various Membranes Using MWNTs as a Modifier

Abstract: Summary: The effect of multi-walled carbon nanotubes (MWNTs) incorporated for the modification of membrane performances was studied. Two different types of membranes were prepared by using MWNTs: one was polysulfone (PSf) ultrafiltration (UF) membrane and the other was polyvinyl alcohol (PVA) pervaporation membrane. The PSf UF membranes with different contents of MWNTs were prepared by the conventional phase inversion process, and used for water-treatment. On the other hand, the PVA membranes with different am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 15 publications
(14 reference statements)
2
20
0
Order By: Relevance
“…Thus the ratio of water to ethanol partial fluxes and the separation factor enhance. Similar results have been reported in the literature [17,27,28]. For example, Shirazi et al [28] prepared PVA-CNT nanocomposite membranes for dehydration of isopropanol aqueous solutions and observed that incorporating CNTs in the PVA matrix significantly increases water separation factor due to rigidification of the polymer chains.…”
Section: Pervaporation Performancesupporting
confidence: 76%
See 1 more Smart Citation
“…Thus the ratio of water to ethanol partial fluxes and the separation factor enhance. Similar results have been reported in the literature [17,27,28]. For example, Shirazi et al [28] prepared PVA-CNT nanocomposite membranes for dehydration of isopropanol aqueous solutions and observed that incorporating CNTs in the PVA matrix significantly increases water separation factor due to rigidification of the polymer chains.…”
Section: Pervaporation Performancesupporting
confidence: 76%
“…Furthermore, several inorganic compounds have been used as filler in the synthesis of the mixed matrix membranes for solvent dehydration by the pervaporation process. For example, zeolite [5][6][7]17,18,23], titanium oxide (TiO 2 ) [24,25], iron [22], sodium montmorillonite clay [26], carbon nanotubes (CNTs) [27][28][29] and silica [30]. There are some drawbacks in the preparation of mixed matrix membranes such as poor distribution of the filler in the polymer matrix and weak contact of inorganic filler particles in the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the initial contact angle of M-4 top surface was about 75°, which drop 12°C in the first 10s and then slowly decreases 57°C in 120s, indicating improved hydrophilicity from the pure CDA membrane. Similar phenomenon had been reported by Choi et al [32]. This result can be explained by the fact that during the phase inversion process, hydrophilic MWCNTs migrated spontaneously to the membrane/water interface to reduce the interface energy [33].…”
Section: Hydrophilicity Of the Blend Membranesupporting
confidence: 87%
“…which was derived from the Hagen-Poiseuille's equation [18]. Here, r, , Â, P, and Q are the pore radius, the interfacial tension of water/i-pentanol, the contact angle at the interface of water phase and polymer, the applied pressure, and the permeate flow rate, respectively.…”
Section: Pore Size Distributionmentioning
confidence: 99%
“…Nowadays, there are more reports on the fluid transport through porous CNTs/polymer membrane. Choi et al prepared acidified-MWNTs/polysulfone (PSf) membranes through an immersed phase inversion process using N-methyl-2-pyrrolidinone (NMP) as a solvent and water as a coagulant [17,18]. Qiu et al prepared MWNTs/PSf membranes containing MWNTs functionalized by isocyanate and isophthaloyl chloride groups via the reaction between carboxylated carbon nanotubes and 5-isocyanato-isophthaloyl chloride [19].…”
Section: Introductionmentioning
confidence: 98%